Розвиток необанкінгу в Україні - Дощин, Денис Олександрович; Doshchyn, Denys Oleksandrovych (Ірпінь, 2024)
З’ясовано особливості цифрової трансформації банківської системи. Досліджено економічний зміст та особливості розвитку необанкігу як одного із провідних драйверів цифрової трансформації банківської системи. Проаналізовано базові показники, що характеризують розвиток необанкінгу у світі. Проведено аналіз сучасних тенденцій розвитку необанкінгу в Україні на фоні світового рівня. Визначено основні перспективи розвитку необанкінгу в Україні.

The peculiarities of the digital transformation of the banking system have been clarified. The economic content and features of the development of neo-banking as one of the leading drivers of the digital transformation of the banking system have been studied. The basic indicators characterizing the development were analyzed neobanking in the world. The analysis of modern trends in the development of neobanking in Ukraine against the background of the world level was carried out. The main prospects for the development of neobanking in Ukraine have been determined.
Development of neobanking in Ukraine
Keywords: необанки; банківська система; Національний банк України; банки; онлайн-банкінг; фінансові технології; non-banks; National Bank of Ukraine; banks; online banking; financial technologies; banking system